Biosafety level-2 laboratory diagnosis of Zaire Ebola virus disease imported from Liberia to Nigeria - Olumuyiwa B. Salu; Ayorinde B. James; Bamidele O. Oke; Mercy R. Orenolu; Roosevelt A. Anyanwu; Maryam A. Abdullah; Christian Happi; Jide Idris; Ismail A. Abdus-Salam; Abdul-Salam Nasidi; Folashade T. Ogunsola; Oyewale Tomori; et al. (AOSIS, 2016)
Introduction: Global travel is an efficient route of transmission for highly infectious pathogens and increases the chances of such pathogens moving from high disease-endemic areas to new regions. We describe the rapid and safe identification of the first imported case of Ebola virus disease in a traveler to Lagos, Nigeria, using conventional reverse transcription polymerase chain reaction (RT-PCR) in a biosafety level (BSL)-2 facility. Case presentation: On 20 July 2014, a traveler arrived from Liberia at Lagos International Airport and was admitted to a private hospital in Lagos, with clinical suspicion of Ebola virus disease. Methodology and Outcome: Blood and urine specimens were collected, transported to the Virology Unit Laboratory at the College of Medicine, University of Lagos, and processed under stringent biosafety conditions for viral RNA extraction. RT-PCR was set-up to query the Ebola, Lassa and Dengue fever viruses. Amplicons for pan-filoviruses were detected as 300 bp bands on a 1.5% agarose gel image; there were no detectable bands for Lassa and Dengue viral RNA. Nucleotide BLAST and phylogenetic analysis of sequence data of the RNA-dependent RNA polymerase (L) gene confirmed the sequence to be Zaire ebolavirus (EBOV/Hsap/ NGA/2014/LIB-NIG 01072014; Genbank: KM251803.1). Conclusion: Our BSL-2 facility in Lagos, Nigeria, was able to safely detect Ebola virus disease using molecular techniques, supporting the reliability of molecular detection of highly infectious viral pathogens under stringent safety guidelines in BSL-2 laboratories. This is a significant lesson for the many under-facilitated laboratories in resource-limited settings, as is predominantly found in sub-Saharan Africa.